2014
DOI: 10.3329/bjms.v13i3.9153
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Histopathological histopathological correlation and detection of anti PGL-1 antibodies in leprosy patients

Abstract: Background: Leprosy (Hansen’s disease) is one of the major health problems of the world especially in developing countries. In India, it was first described in “Sushruta Samhita” & treated by Chaulmoogra oil and caused by Mycobacterium Leprae. Early diagnosis of leprosy, an absolute necessity for control as well as effective therapy. For this, clinical diagnosis, skin smear examination is adequate coupled with histo-pathological examination of skin and nerve lesions with modified Fite Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(Karim et al, 2015). The MLPA test can be used not only in diagnosing MB type leprosy cases but also for treatment evaluation (Datta et al, 2014). Our study showed that IgM anti PGL-1 was decreased 6 months after treatment, it means that the MDT regimen administered for 6 months may provide improvement in leprosy patients.…”
Section: Discussionmentioning
confidence: 63%
“…(Karim et al, 2015). The MLPA test can be used not only in diagnosing MB type leprosy cases but also for treatment evaluation (Datta et al, 2014). Our study showed that IgM anti PGL-1 was decreased 6 months after treatment, it means that the MDT regimen administered for 6 months may provide improvement in leprosy patients.…”
Section: Discussionmentioning
confidence: 63%